Clinical application of digital pathology in small intestinal neuroendocrine tumours: proposal of a new G0 category - Nathalie Guedj; Guillaume Cléry; Anaïs Chassac; Nathalie Colnot; Vinciane Rebours; Jérôme Cros; Louis de Mestier; Anne Couvelard; Matthieu Tihy (Endocrine Oncology, 2026)
Abstract Introduction Small intestinal neuroendocrine tumours (siNETs) are usually indolent neoplasms, most classified as grade 1 with very low proliferative activity. In practice, Ki-67 in G1 siNETs is often reported simply as “<3%”, limiting prognostic discrimination. Digital pathology now enables reliable automated quantification of very low Ki-67 values. We investigated whether precise Ki-67 quantification could improve prognostic stratification in G1 siNETs. Methods We retrospectively included 63 consecutive patients who underwent surgery for a G1 siNET at Beaujon Hospital between 2001 and 2017. Ki-67 was quantified on primary tumours (PT) and, when available, lymph-node and liver metastases , using QuPath automated image analysis. Ki-67 was assessed in the highest-proliferation hotspot (0.4 mm2; >2,000 tumour cells; Ki-67max) and as the mean of five hotspots (Ki-67mean). The primary endpoint was recurrence-free survival (RFS). Results Among 63 patients, 33 underwent curative-intent surgery (median age 56 years; 69% male). Median tumour size was 20 mm. At surgery, 87% were node-positive and 67% had synchronous metastases. Median Ki-67max/Ki-67mean in PTs was 0.99%/0.71%. In localized disease, Ki-67max predicted RFS (AUROC=0.84). Median follow-up was 60.2 months. Median RFS was 112 months in patients with Ki-67max ≥1%, whereas no recurrences occurred in those with Ki-67max <1% (p=0.04). Ki-67mean provided no additional prognostic value. Conclusion Precise digital Ki-67 quantification refines prognostic stratification in G1 siNETs. Tumours with Ki-67 <1% may represent a biologically distinct “G0” subgroup associated with extremely low recurrence risk after curative surgery.